The structure of the Dark Triad traits: A network analysis. (1st December 2020) - Trahair, Cassidy; Baran, Lidia; Flakus, Maria; Kowalski, Christopher Marcin; Rogoza, Radosław
Abstract: Growing interest in the exploration of the dark side of personality recently led to the questions concerning the number, distinctiveness, and structural organization of its components. The main goal of the current study ( N  = 1012) is to explore the structure of the Dark Triad traits using the network approach. The results showed that all of the traits formed a single network forming two dimensions. However, agentic facets of narcissism were least related to Machiavellianism and psychopathy, which suggests the partial distinctiveness of the trait. Also, the antagonistic facet of narcissism mediated the relations between most of the agentic facets of narcissism and Machiavellianism and psychopathy. Finally, Machiavellianism and psychopathy were located in close proximity, which reflects their core status in the Dark Triad. The interpretation of the results and limitations of the study are further discussed.